2015
DOI: 10.1093/nar/gkv629
|View full text |Cite
|
Sign up to set email alerts
|

Mediator tail subunits can form amyloid-like aggregatesin vivoand affect stress response in yeast

Abstract: The Med2, Med3 and Med15 proteins form a heterotrimeric subdomain in the budding yeast Mediator complex. This Med15 module is an important target for many gene specific transcription activators. A previous proteome wide screen in yeast identified Med3 as a protein with priogenic potential. In the present work, we have extended this observation and demonstrate that both Med3 and Med15 form amyloid-like protein aggregates under H2O2 stress conditions. Amyloid formation can also be stimulated by overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Additionally, we tested the phenotypes of the med15BΔ and HTUΔ/CgMED15B strains under different biological stimuli and found that Med15B was essential for cell tolerance under oxidative and osmotic stress conditions (data not shown). These data are consistent with Med15 from S. cerevisiae having a critical role in the stress response (20,21,32). Our results indicated that Med15B has a vital modulatory role in pH homeostasis in C. glabrata, so it will be important to examine this function in other eukaryotes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, we tested the phenotypes of the med15BΔ and HTUΔ/CgMED15B strains under different biological stimuli and found that Med15B was essential for cell tolerance under oxidative and osmotic stress conditions (data not shown). These data are consistent with Med15 from S. cerevisiae having a critical role in the stress response (20,21,32). Our results indicated that Med15B has a vital modulatory role in pH homeostasis in C. glabrata, so it will be important to examine this function in other eukaryotes.…”
Section: Discussionsupporting
confidence: 89%
“…The tail module subunits Med2, Med3, and Med15 can form a subcomplex and are involved in a heat shock response through recruitment by activated heat shock transcription factor 1 (Hsf1) to its target genes (19). By changing the Mediator subunit composition, the tail subcomplex affects the response to oxidative stress (20). The tail module subunits are also required for mitogen-activated protein kinase (MAPK) Hog1-mediated gene expression, which is essential for proper cell adaptation to osmotic stress (21).…”
mentioning
confidence: 99%
“…Med15 makes multiple contacts with Gcn4 including polymorphic polyQ repeats and KIX domain (Jedidi et al 2010). Overexpression of Med15 causes protein aggregation, presumably via the polyQ and polyQA regions of this region alone aggregates in response to hydrogen peroxide (Zhu et al 2015). Overexpression of the first polyQ and polyQA of Med15 reduces cell growth in unstressed cells and salt exposed yeast but rescues growth in the presence of rapamycin (8).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Med15 causes protein aggregation, presumably via the polyQ and polyQA regions of this region alone aggregates in response to hydrogen peroxide (Zhu et al 2015). Overexpression of the first polyQ and polyQA of Med15 reduces cell growth in unstressed cells and salt exposed yeast but rescues growth in the presence of rapamycin (8). Full-length Med15 also forms cytosolic foci in yeast exposed to hydrogen peroxide (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation